Obesity among school-age children from Zakho (Kurdistan, Iraq) is linked to viewing screen media - Farhad Shaker Armishty; Ronahi Younis Ibrahim; Adam J. Adam; Racheen S. Haji; Zeen Khalil Ghazi; Parwar I. Tahir (Zaslavsky O.Yu., 2023)
Background. Healthcare systems are very concerned about childhood obesity, which continues to be a barrier to medical innovation. Over the last three decades, the frequency of childhood overweight/ obesity has increased significantly. Children spend a significant amount of time in front of electronic devices such as cell phones, games, computers, and television that is linked to a decreased physical activity and weight gain. The purpose of the study was to find the association between watching screen media and obesity in school-aged children from Zakho. Materials and methods. This is a cross-sectional, case-control, face-to-face survey study. All students aged 9-15 years from different schools were invited to complete the questionnaire. Well-trained medical students collected the anthropometric measurements of weight and height. Results. A total of 500 students between 9 and 15 years were interviewed. Approximately 72 % of them were males and 28 % were females. There was a significant association between a history of eating while watching screens and obesity (P = 0.003), as well as between the average number of hours spent daily using a computer and obesity (P = 0.016). Conclusions. In summary, this study supported the link between screen usage and childhood obesity in school-aged children. As a result, it is vital to create health promotion initiatives that emphasize a healthy 24-hour period, which includes a balanced amount of time spent engaging in physical activity, watching television, and sleeping.